(untitled) (Jurnal Ilmiah dr. Aloei Saboe, 2024)
This literature review examines the pharmacokinetic profile of nonsteroidal anti-inflammatory drugs (NSAIDs) in the geriatric population. Given the high prevalence of chronic conditions requiring NSAID use among the elderly, understanding the pharmacokinetic alterations due to physiological changes in this age group is crucial. The review highlights key findings from recent studies, showing that elderly patients are more susceptible to adverse effects due to altered drug absorption, distribution, metabolism, and excretion. It also emphasizes the importance of appropriate dosing, careful monitoring, and the potential of alternative therapies like warm moringa leaf compresses for managing pain. Furthermore, the review underlines the necessity for improved prescribing practices and the development of detailed clinical guidelines to ensure the safe and effective use of NSAIDs in the geriatric population.